Diet and feeding habits of the small catfish, Clarias liocephalus in wetlands of Western Uganda - Yatuha, Jane; Kang’ombe, Jeremiah; Chapman, Lauren (African Journal of Ecology, 2012)
Clarias liocephalus is an air-breathing catfish inhabiting wetland and river systems in East Africa. This catfish is in high demand for sale as live bait in the Nile perch fishery of Lake Victoria and equally important in the diet of local communities in the lake basin. Wetland loss and increasing fishing pressure potentially threaten the persistence of C. liocephalus; however, little information exists on the ecology of this species to permit evaluation of current threats. This study quantified dietary characteristics of C. liocephalus from heavy and lightly fished wetlands in Western Uganda using numeric, gravimetric and volumetric indices on 492 stomach samples collected over one year. Clarias liocephalus was significantly smaller in three heavily fished sites, relative to the one in-park site, likely a reflection of a size-selective fishery. Across sites, C. liocephalus was a generalist feeder whose diet was dominated by aquatic dipteran larvae and plant material. The broad niche gives C. liocephalus an ecological advantage to forage effectively on a wide selection of prey. The significant presence of plant material shows that the species may utilize plant protein, an important consideration of diet requirements should the species be selected for aquaculture.
Keywords: Papyrus swamp; clariid catfish; stomach contents